Hybridization between Music and Image in Cinema: A Medio-logical Approach (The International Journal of Educational Sciences and Arts, 2026)
When the eye meets the ear, a hybrid artistic form is born, where visual and auditory languages merge to create new forms of expression. "The concept of hybridity, in its original linguistic sense, refers to the combination of two distinct elements to produce a new composite form that brings together their respective characteristics. This concept has moved from the field of biology to the domains of the humanities and the arts, becoming one of the fundamental notions for understanding the transformations of contemporary creativity and the intersection of artistic genres and media. Cinema, as a composite art form based on the interaction of image, sound, movement, and time, represents one of the most significant fields in which artistic hybridization processes are manifested.This research examines the hybridity between the two media of music and image within cinematic discourse, by analysing the interactive relationship between the auditory and visual dimensions. This relationship is not limited to mere accompaniment or parallelism; rather, it contributes to the shared production of aesthetic and expressive meaning. The study is guided by a central research question: How does the hybridization of music and image contribute to the production of a cinematic language that transcends traditional boundaries between the arts? And how can this interaction be understood through the mediological approach of Régis Debray, which considers the medium not merely as a vehicle for meaning, but as an active element in its production and in shaping modes of perception and reception?
Keywords: Hybridization; Mediology; Music; Image; Cinema